Clinical and Microbiological Characteristics of Fungal Keratitis in the United States, 2001–2007: A Multicenter Study - Keay, Lisa J. (2011)
OBJECTIVE: To study the epidemiology, clinical observations, and microbiologic characteristics of fungal keratitis at tertiary eye care centers in the United States. DESIGN: Retrospective multicenter case series. PARTICIPANTS: Fungal keratitis cases presenting to participating tertiary eye care centers. METHODS: Charts were reviewed for all fungal keratitis cases confirmed by culture, histology, or confocal microscopy between January 1, 2001, and December 31, 2007, at 11 tertiary clinical sites in the United States. MAIN OUTCOME MEASURES: Frequency of potential predisposing factors and associations between these factors and fungal species. RESULTS: A total of 733 cases of fungal keratitis were identified. Most cases were confirmed by culture from corneal scraping (n = 693) or biopsies (n = 19); 16 cases were diagnosed by microscopic examination of corneal scraping alone; and 5 cases were diagnosed by confocal microscopy alone. Some 268 of 733 cases (37%) were associated with refractive contact lens wear, 180 of 733 cases (25%) were associated with ocular trauma, and 209 of 733 cases (29%) were associated with ocular surface disease. No predisposing factor was identified in 76 cases (10%). Filamentous fungi were identified in 141 of 180 ocular trauma cases (78%) and in 231 of 268 refractive contact lens-associated cases (86%). Yeast was the causative organism in 111 of 209 cases (53%) associated with ocular surface disease. Yeast accounted for few cases of fungal keratitis associated with refractive contact-lens wear (20 cases), therapeutic contact-lens wear (11 cases), or ocular trauma (21 cases). Surgical intervention was undertaken in 26% of cases and was most frequently performed for fungal keratitis associated with ocular surface disease (44%). Surgical intervention was more likely in cases associated with filamentous fungi (P = 0.03). Among contact lens wearers, delay in diagnosis of 2 or more weeks increased the likelihood of surgery (age-adjusted odds ratio = 2.2; 95% confidence interval, 1.2–4.2). CONCLUSIONS: Trauma, contact lens wear, and ocular surface disease predispose patients to developing fungal keratitis. Filamentous fungi are most frequently the causative organism for fungal keratitis associated with trauma or contact lens wear, whereas yeast is most frequently the causative organism in patients with ocular surface disease. Delay in diagnosis increases the likelihood of surgical intervention for contact lens-associated fungal keratitis. FINANCIAL DISCLOSURE(S): Proprietary or commercial disclosure may be found after the references.